PERAN KEPEMIMPINAN KEPALA SD NEGERI 1 KETEWEL DALAM MANAJEMEN BERBASIS SEKOLAH - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; I Gusti Ngurah Bagus Mahendra Adhiputra; Ni Kadek Candra Kusuma Dewi; Ni Putu Trisna Dewi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study is motivated by the importance of the principal’s leadership role in improving educational quality through effective school management. The purpose of this study is to describe the role of the principal in the implementation of school-based management at SD Negeri 1 Ketewel. This research employs a qualitative descriptive approach. Data were collected through observation and interviews and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results show that the principal is able to perform roles as a leader, manager, motivator, and evaluator effectively. This is reflected in the management of human resources based on individual potential, continuous motivation for teachers, and ongoing evaluation practices. These efforts have contributed to the improvement of school quality and increased public trust. Therefore, the principal’s leadership plays a significant role in successful school management.